Direct seeding of Pinus Sylvestris using microsite preparation and invigorated seed lots of different quality: 2-year results - Winsa, Hans; Bergsten, Urban (Canadian Journal of Forest Research, 1994)
Direct seeding of Pinussylvestris L. is a regeneration method, with potential for development considering scarification, microsite preparation, seed invigoration, and seed quality. Three seed lots of different quality concerning seed weight, germination percent, and mean germination time were used on two sites in northern Sweden. Microsite preparation, 2 cm deep pyramidal indentations, of the mineral soil improved seedling emergence on the two sites by 48 and 62%, respectively, compared with seeding without preparation other than removal of the humus layer. Microsite preparation in combination with invigorated seed, i.e., seed incubated at 30% moisture content for 7 days at 15 °C, resulted in seedling emergence of about 85% for the highest and about 50% for the lowest seed quality at both sites. Noninvigorated seed, seeded without microsite preparation, reached about 55% for the highest and 22% at one and 43% at the other for the lowest seed quality. Without microsite preparation there was no, or a negative, effect of seed invigoration on seedling emergence. Seedling survival after the first winter improved significantly with better seed quality. Survival averaged 92 and 72% at the two sites, with frost heaving causing most mortality. Seedlings from invigorated and redried seed survived better than seedlings from untreated seed. Seedlings from the best seed quality had higher values in seedling height, about 35%, shoot length, about 60%, and needle length, about 30%, after two growing seasons than seedlings from lower seed qualities. Invigoration and microsite preparation had no effect on measured growth characteristics.